Relationships among Tomistoma schlegelii in Malaysia Based on Cyt b-Control Region Gene Analysis - Md Adzhar, Muhammad Amirul Arib; Hassan, Ruhana (International Journal of Zoology, 2017)
Tomistoma schlegelii is a slender snout crocodile, secretive in nature which is currently under Appendix I of Convention on International Trade in Endangered Species of Wild Flora and Fauna (CITES). Limited information is currently available on its wild population, especially in Malaysia. Thus this study aims to describe genetic relationship of T. schlegelii populations from Malaysia which was done using partial sequencing of Cytochrome b-control region mtDNA gene. The study reveals that the genetic diversity among T. schlegelii is high, ranging from 0.16% to 3.34%, suggesting healthy populations. Analysis showed that there is gene flow among populations (Da = 1.71% to 2.21%) within Western Sarawak, Peninsular Malaysia, and other geographical regions coherent with Sundaland theory, suggesting that there is ancient river system connecting the two regions of Peninsular Malaysia and West Borneo when the Sunda Shelf was exposed. Unique haplotypes had been observed in Northern Sarawak (SAM01 and SAM02) as well as in Sumatera; thus each T. schlegelii deserved its own management strategies to ensure the survival of the species.